Performance of Single-Shot Echo-Planar Imaging in Diffusion Tensor Imaging in Rat Sciatic Nerve Compared With Readout-Segmented Echo-Planar Imaging - Chen, Yueyao; Pan, Zhongxian; Meng, Fanqi; Li, Zhujing; Hu, Yuanming; Yu, Xuewen; Gao, Jinyun; Guo, Yihao; Lyu, Hanqing; Lin, Xiaofeng (Frontiers in Neuroscience, 2022)
Objectives: To compare the performances of single-shot echo-planar imaging (SS-EPI) and readout-segmented echo-planar imaging (RS-EPI) for diffusion tensor imaging (DTI) of the rat sciatic nerve. Methods: Eight healthy adult male Sprague-Dawley rats were anaesthetized and scanned with a 3T magnetic resonance imaging (MRI) scanner using SS-EPI and RS-EPI DTI sequences. The image quality in terms of morphology of the nerve, distortions of the nearby femur, muscles, and homogeneous of neuromuscular were evaluated and scored. The correlations between the DTI parameters including fractional anisotropy (FA), axial diffusivity (AD), radial diffusivity (RD), and apparent diffusion coefficient (ADC), and histopathological parameters were calculated by using the Pearson correlation coefficient and compared by the modified Fisher Z-transform respectively. Results: The quality scores were higher for the images from the SS-EPI sequence compared with the RS-EPI sequence for characteristics such as sharpness of the sciatic nerve margin (P = 0.008), artifacts of the sciatic nerve (P = 0.008), and homogeneity of the neuromuscular region (P = 0.007), as well as the contrast-to-noise ratio (CNR) of DW images (P < 0.001). The correlation coefficients were higher for the FA and RD values from the SS-EPI sequence compared with those from the RS-EPI sequence. Furthermore, the correlation coefficients between FA and myelin thickness (P = 0.027), FA and diameter of the myelinated fibre (P = 0.036), as well as RD and myelin thickness (P = 0.05) were statistically higher for the SS-EPI sequence compared with those for the RS-EPI sequence. Conclusions: DTI analysis of the rat sciatic nerve showed that the image quality from the SS-EPI sequence was significantly higher compared with that from the RS-EPI sequence. Furthermore, the FA and RD derived from the SS-EPI sequence are promising and sensitive biomarkers to detect the histopathological changes in the rat sciatic nerve.